Blueberry Juice Attenuates Pulmonary Fibrosis via Blocking the TGF-β1/Smad Signaling Pathway - Yali Li; Yali Li; Yali Li; Liqun Wang; Qianyu Zhang; Li Tian; Cailing Gan; Hongyao Liu; Wenya Yin; Tinghong Ye (Frontiers Media S.A., 2022)
Idiopathic pulmonary fibrosis (IPF) is a progressive, fatal, and chronic lung disease, lacking a validated and effective therapy. Blueberry has demonstrated multiple pharmacological activities including anti-inflammatory, antioxidant, and anticancer. Therefore, the objective of this study was to investigate whether blueberry juice (BBJ) could ameliorate IPF. Experiments in vitro revealed that BBJ could significantly reduce the expressions of TGF-β1 modulated fibrotic protein, which were involved in the cascade of fibrosis in NIH/3T3 cells and human pulmonary fibroblasts. In addition, for rat primary lung fibroblasts (RPLFs), BBJ promoted the cell apoptosis along with reducing the expressions of α-SMA, vimentin, and collagen I, while increasing the E-cadherin level. Furthermore, BBJ could reverse epithelial-mesenchymal transition (EMT) phenotypic changes and inhibit cell migration, along with inducing the upregulation of E-cadherin in A549 cells. Compared with the vehicle group, BBJ treatment alleviated fibrotic pathological changes and collagen deposition in both bleomycin-induced prevention and treatment pulmonary fibrosis models. In fibrotic lung tissues, BBJ remarkably suppressed the expressions of collagen I, α-SMA, and vimentin and improved E-cadherin, which may be related to its inhibition of the TGF-β1/Smad pathway and anti-inflammation efficacy. Taken together, these findings comprehensively proved that BBJ could effectively prevent and attenuate idiopathic pulmonary fibrosis via suppressing EMT and the TGF-β1/Smad signaling pathway.